Mucocutaneous Manifestations of Inflammatory Bowel Disease (2021)
ABSTRACT: Inflammatory bowel disease (IBD) is a chronic and incurable disease, of unknown etiology, associated with an unregulated immune response to environmental triggers in a genetically predisposed host. IBD affects mainly the gastrointestinal (GI) tract and includes Crohn's disease (CD) and ulcerative colitis (UC). However, a large percentage of patients may present with extraintestinal manifestations, including mucocutaneous ones (which are the most common) and dermatologic findings, such as erythema nodosum, pyoderma gangrenosum, and aphthous stomatitis (which are the most frequently occurring). According to pathophysiologic mechanisms, mucocutaneous manifestations of IBD are classified into five categories, namely, specific manifestations, associated manifestations, reactive manifestations, adverse effects of IBD therapy, and malabsorption manifestations. Recognizing such manifestations should not be performed only by a dermatologist but also other specialties such as internal medicine, gastroenterology, among others. This is because these manifestations can present before the IBD diagnosis, even in the absence of GI symptoms. Therefore, these skin lesions could be a fundamental tool for the earlier diagnosis of IBD. This review provides a comprehensive overview of the most common cutaneous manifestations of IBD with a focus on their epidemiology, diagnostic criteria, clinical presentation, and available medical treatment